'Community of Inquiry' method and ESL Learners' speaking skill - Preece, Abdul Shakour Duncan; Bularafa, Mohammed Waziri (2015)
The research explored the effects of 'Community of Inquiry' (COI) method on the elementary school students' speaking skill. The participants comprised of twenty five ESL learners of beginner and pre-intermediate level at a private school in Kuala Lumpur. The sample included four male and three female students in grade five. Qualitative research method was used to investigate learners' use of spoken English during the COI discussions. Seven sessions, lasting one hour each were video-taped and analyzed using content analysis, focusing upon Fascione's (2006) six critical thinking skills, namely: interpretation, analysis, explanation, evaluation, inference and self-regulation. The findings showed that through cooperation and imitation, five of the six critical thinking skills were practiced by students with the exception of 'self-regulation'. Moreover, specific grammar and vocabulary items were prevalent in learners' speaking. For example: the First Conditional was used to offer solutions and alternatives; Present Simple was employed when defining concepts or stating facts; and Past Simple was used when students narrated their experiences to explain or support ideas and opinions. It is clear that COI provides valuable opportunities for students to express themselves and practice their listening and speaking skills. As such, it represents a good method for introduction into mainstream Malaysian public schools, especially ESL.